2008
DOI: 10.1038/gt.2008.113
|View full text |Cite
|
Sign up to set email alerts
|

Persistent episomal transgene expression in liver following delivery of a scaffold/matrix attachment region containing non-viral vector

Abstract: An ideal gene therapy vector should enable persistent transgene expression without limitations of safety and reproducibility. Here we report the development of a non-viral episomal plasmid DNA (pDNA) vector that appears to fulfil these criteria. This pDNA vector combines a scaffold/matrix attachment region (S/MAR) with a human liver-specific promoter (alpha1-antitrypsin (AAT)) in such a way that long-term expression is enabled in murine liver following hydrodynamic injection. Long-term expression is demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 49 publications
5
96
1
2
Order By: Relevance
“…8 Our study shows that the protection provided by Bcl-2 to S/MAR-transfected hepatocytes was sufficient to achieve mitotic stability of a small proportion of S/MAR plasmid-containing hepatocytes in vivo. It has been previously reported that established cell clones containing S/MAR plasmids are found exclusively in euchromatin nuclear compartments of active transcription 18 and are associated with histone markers of active transcription (such as H3K4m3, H3K4m1 and H3K36m3) during most phases of the cell cycle.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…8 Our study shows that the protection provided by Bcl-2 to S/MAR-transfected hepatocytes was sufficient to achieve mitotic stability of a small proportion of S/MAR plasmid-containing hepatocytes in vivo. It has been previously reported that established cell clones containing S/MAR plasmids are found exclusively in euchromatin nuclear compartments of active transcription 18 and are associated with histone markers of active transcription (such as H3K4m3, H3K4m1 and H3K36m3) during most phases of the cell cycle.…”
Section: Discussionmentioning
confidence: 60%
“…8 For the experiments presented here we used this vector as a basis for the construction of a biscistronic expression cassette in which Bcl-2 is positioned as the first transcribed gene to provide high levels of Bcl-2 for protection against Fas-induced apoptosis, while expression of the second transgene luciferase permits evaluation of plasmid fate over time. The new S/MAR plasmid is called pBcLucA1 and its control without the S/MAR element is called pBcLucA1 Control.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations